HOLISTICS JOURNAL HOSPITALITY AND LINGUISTICS: Analysis of Difficulties in Understanding Ambiguous Meaning in Recount Text of the Tenth Grade Students of Senior High School 12 Palembang - Muhammad Ali (HOLISTICS, 2021)
The title of this research “Analysis of Difficulties in Understanding Ambiguous Meaning in Recount Text of the Tenth Grade Students of Senior High School 12 Palembang.” The objective of this study to find out the problems in understanding ambiguous meaning in the recount text faced by the tenth-grade students of Senior High School 12 Palembang. Qualitative method was used in this study. 10 students in the tenth grade were chosen as the participants in this study. The result showed that the students were difficult in understanding ambiguous meaning in recount text especially lexical ambiguity and the participants were not able to answer a lot of ambiguous meaning which means that the students’ knowledge of ambiguous meaning greatly needs to be increased to know kinds of ambiguous. There are four reasons why the students felt difficult in understanding ambiguous meaning in recount text: ambiguous sentence has confusing meanings; ambiguous sentence is difficult because they had to analyze all parts of the sentence without any mistakes; ambiguous sentence is difficult because they had to analyze the deepest meaning from the sentence that showed an ambiguity; and ambiguous meaning is difficult because it has more than one meaning.